An anti-icing coating material suitable for wind turbine blades and a method of making the same

CN122234676BActive Publication Date: 2026-10-27马鞍山采石矶涂料有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610679381.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-18
Publication Date
2026-10-27
Estimated Expiration
2046-05-18

AI Technical Summary

Technical Problem

[0004]然而,现有的超疏水防冰涂层依旧存在一定的技术缺陷,例如:1)现有涂料中通常添加纳米二氧化硅、碳纳米管等光热性功能填料,以便于涂层在太阳光的照射下,能够将太阳能转化为热能而加热涂层表面,使得涂层表面温度高于环境温度,从而抑制结冰或加速冰融化来达到有效防结冰/除冰的目的,然而这些功能填料因表面能高、极性差异大,在树脂基体中极易发生团聚和沉降,导致涂层稳定性差,无法充分发挥其防结冰/除冰的目的冰;针对此问题,目前主要是采用硅烷偶联剂对填料进行表面处理,但是小分子偶联剂分散效果有限,且填料与树脂基体的界面结合强度不足,在长期服役过程中填料易脱落,导致涂层性能快速衰减;2)现有防冰涂层通常仅关注疏水性能,忽视了风电叶片实际服役环境中对防腐蚀、耐候性、耐磨性的综合需求,风电叶片在海洋、高海拔等环境中长期服役,不仅需要防结冰,还需要抵抗盐雾腐蚀、紫外线老化、风沙冲蚀等多重环境应力,现有的防冰涂层显然是无法满足风电叶片多重防护需求;3)现有的超疏水涂层依赖微纳粗糙结构实现疏水效果,但该结构在风沙冲蚀、冰层剥离等机械作用下易被破坏,导致防冰性能快速衰减,涂层有效寿命短

Benefits of technology

本发明提供的涂料,具有优异的防结冰功能、耐候性、防腐蚀性、耐磨性,综合性能优异,能够很好的满足风电叶片防结冰涂料的使用要求,具有极强的工业应用价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses an anti-icing coating suitable for wind power blades and a preparation method thereof. The coating comprises an A component and a B component, and the mass ratio of the A component and the B component is (6-10):1. The A component is prepared from raw materials in the following mass fractions: fluorosilicon-acrylic hybrid resin, modified functional composite filler, polytetrafluoroethylene micro powder, auxiliary reinforcing agent, dispersing agent, leveling agent and solvent. The B component is an elastic polyurethane curing agent. The coating has excellent anti-icing function, weather resistance, corrosion resistance and wear resistance, and has excellent comprehensive performance, can well meet the use requirements of the wind power blade anti-icing coating, and has extremely strong industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an anti-icing coating suitable for wind turbine blades and its preparation method, belonging to the technical field of wind turbine blade protective coatings. Background Technology

[0002] As a crucial component of clean energy, wind power generation has seen its installed capacity grow rapidly and continuously. Wind turbine blades, as key components of wind turbine units, are exposed to harsh environments of high humidity and low temperatures for extended periods, facing severe surface icing problems. Blade icing alters the aerodynamic shape of the blades, leading to a decrease in lift coefficient and an increase in drag coefficient. In severe cases, it can reduce the aerodynamic efficiency of the wind turbine by more than 30%, and even cause unit shutdowns and safety accidents.

[0003] Currently, both domestically and internationally, the main technologies used in wind turbine blade anti-icing are active de-icing and passive anti-icing. Active de-icing includes methods such as electrothermal de-icing, mechanical de-icing, and chemical de-icing, but these methods generally suffer from high energy consumption, low efficiency, and complex equipment modifications. Passive anti-icing is mainly achieved through coating technology, among which superhydrophobic coatings have attracted widespread attention due to their unique water-repellent properties.

[0004] However, existing superhydrophobic anti-icing coatings still have certain technical shortcomings, such as: 1) Existing coatings typically add photothermal functional fillers such as nano-silica and carbon nanotubes so that the coating can convert solar energy into heat energy under sunlight to heat the coating surface, making the coating surface temperature higher than the ambient temperature, thereby inhibiting icing or accelerating ice melting to achieve the purpose of effective anti-icing / de-icing. However, these functional fillers, due to their high surface energy and large polarity differences, are prone to agglomeration and sedimentation in the resin matrix, resulting in poor coating stability and failing to fully realize their purpose of anti-icing / de-icing. To address this problem, silane coupling agents are currently mainly used to treat the fillers on the surface, but the dispersion effect of small molecule coupling agents is limited, and... 1) Insufficient interfacial bonding strength between filler and resin matrix leads to easy filler detachment during long-term service, resulting in rapid degradation of coating performance; 2) Existing anti-icing coatings usually only focus on hydrophobic properties, ignoring the comprehensive requirements of wind turbine blades for corrosion resistance, weather resistance, and wear resistance in actual service environments. Wind turbine blades operate for a long time in marine, high-altitude, and other environments, requiring not only anti-icing but also resistance to multiple environmental stresses such as salt spray corrosion, ultraviolet aging, and wind and sand erosion. Existing anti-icing coatings obviously cannot meet the multiple protection requirements of wind turbine blades; 3) Existing superhydrophobic coatings rely on micro-nano rough structures to achieve hydrophobic effects, but this structure is easily damaged under mechanical actions such as wind and sand erosion and ice peeling, leading to rapid degradation of anti-icing performance and short effective life of the coating.

[0005] Therefore, developing an anti-icing coating suitable for wind turbine blades that combines corrosion resistance, weather resistance, and wear resistance has significant industrial value and practical implications. Summary of the Invention

[0006] To address the aforementioned problems in the existing technology, the purpose of this invention is to provide an anti-icing coating suitable for wind turbine blades and its preparation method.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: An anti-icing coating for wind turbine blades comprises component A and component B, wherein the mass ratio of component A to component B is (6-10):1; component A is prepared from raw materials comprising the following mass parts: Fluorosilicone-acrylic hybrid resin: 25-35 parts by weight; Modified functional composite filler: 35-45 parts by weight; Polytetrafluoroethylene micro powder: 3-6 parts by weight; Auxiliary reinforcing agent: 5-12 parts by weight; Dispersant: 0.5-1.5 parts by weight; Leveling agent: 0.2-0.8 parts by weight; Solvent: 20-40 parts by weight; Component B is an elastic polyurethane curing agent; The fluorosilicone-acrylic hybrid resin is obtained by free radical copolymerization of a monomer composition comprising methyl methacrylate, isobornyl methacrylate, butyl acrylate, tridecafluorooctyl methacrylate, vinyl-terminated fluorosilicone oil, hydroxyethyl methacrylate and glycidyl methacrylate. The modified functional composite filler is obtained by modifying aluminum tripolyphosphate, nano-silica, and carboxylated multi-walled carbon nanotubes with fluorinated hyperbranched polyoxysilane; the fluorinated hyperbranched polyoxysilane is obtained by the hydrolysis and condensation reaction of γ-glycidoxypropyltrimethoxysilane, perfluorodecyltrimethoxysilane, hexadecyltrimethoxysilane, and triethoxysilylpropylphosphonic acid. The auxiliary reinforcing agent is prepared by a combination of ring-opening metamerization and hydrosilylation reaction of raw materials comprising norbornene dodecafluoroheptyl ester (NDF), trifluoroethyl methacrylate (TFEMA), dinorbornene ethylene glycol ester (NEG), crosslinking agent, platinum-catalyzed hydrosilylation system, ring-opening metamerization catalyst, chain extender containing dynamic disulfide bonds, and lubricant.

[0008] In one embodiment, the anti-icing coating uses a solvent that is a mixture of propylene glycol methyl ether acetate and butyl acetate in a volume ratio of 1:1; the dispersant is BYK-163; the leveling agent is BYK-333; and the elastic polyurethane curing agent is HDI trimer.

[0009] In one embodiment, the monomer ratio in the fluorosilicone-acrylic hybrid resin is as follows: methyl methacrylate (MMA) 30-40 parts by weight, isobornyl methacrylate (IBOMA) 10-15 parts by weight, butyl acrylate (BA) 15-20 parts by weight, tridecafluorooctyl methacrylate (PFOMA) 10-15 parts by weight, vinyl-terminated fluorosilicone oil (Vi-PDMS-F) 5-10 parts by weight, hydroxyethyl methacrylate (HEMA) 5-8 parts by weight, and glycidyl methacrylate (GMA) 2-5 parts by weight.

[0010] In a preferred embodiment, the preparation of the fluorosilicone-acrylic hybrid resin includes the following steps: 1) Mix methyl methacrylate, isobornyl methacrylate, butyl acrylate, tridecyl fluorooctyl methacrylate, vinyl-terminated fluorosilicone oil, hydroxyethyl methacrylate and glycidyl methacrylate evenly to obtain a monomer mixture; The initiator is dissolved in part of the reaction solvent to obtain an initiator solution; 2) Add the remaining reaction solvent to the reactor, heat to 75-85℃, and then, under nitrogen protection, simultaneously add the monomer mixture (dropping time 2-3 hours) and 80-90% of the initiator solution (dropping time 2.5-3.5 hours). During the dropping process, maintain the reaction temperature at 75-85℃. After the dropping is complete, keep the reaction at this temperature for 2-3 hours, then add the remaining 10-20% of the initiator solution, continue to keep the temperature at this temperature for 1-2 hours, end the reaction, cool to below 60℃, filter and discharge to obtain the fluorosilicone-acrylic hybrid resin.

[0011] In a preferred embodiment, during the preparation of the fluorosilicone-acrylic hybrid resin, the amount of initiator is 0.5-1% of the total mass of the monomers; and the amount of reaction solvent is 1-2 times the total mass of the monomers.

[0012] In a preferred embodiment, during the preparation of the fluorosilicone-acrylic hybrid resin, the initiator is azobisisobutyronitrile (AIBN), and the reaction solvent is a mixed solvent of propylene glycol methyl ether acetate and butyl acetate in a volume ratio of 1:1.

[0013] In one embodiment, the molar ratio of γ-glycidoxypropyltrimethoxysilane (KH-560): perfluorodecyltrimethoxysilane (FDTS): hexadecyltrimethoxysilane (HDTMS): triethoxysilylpropylphosphonic acid in the fluorinated hyperbranched polyoxysilane is (3.0-5.0): (2.0-3.0): (1.5-2.5): (0.5-1.5).

[0014] In a preferred embodiment, the preparation of the fluorinated hyperbranched polyoxysilane includes the following steps: ① Add γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) and solvent to the reaction vessel, under nitrogen protection, and stir at 50-60℃ for 20-40 minutes; ② Add an aqueous solution of acetic acid with a pH of 4-5 dropwise over a period of 0.5-1.5 hours. After the addition is complete, allow the mixture to react at 70-75°C for 2.5-3.5 hours. ③ Slowly add perfluorodecyltrimethoxysilane (FDTS), hexadecyltrimethoxysilane (HDTMS) and triethoxysilylpropylphosphonic acid, stir for 10-20 minutes, then add the organic bismuth catalyst and continue the reaction at 70-75℃ for 2.5-3.5 hours; ④ Cool to 50-60℃, add activated carbon, stir for 20-40 minutes, filter, and distill the filtrate under reduced pressure to obtain fluorinated hyperbranched polyoxysilane.

[0015] In a preferred embodiment, in step ①, the solvent is a mixed solvent of ethanol and ethyl acetate in a volume ratio of 1:2, and the amount of solvent used is 1.5-2.5 times the total mass of silane; in step ②, in the acetic acid aqueous solution, the amount of deionized water is 0.15-0.25 times the total mass of silane, and the amount of glacial acetic acid is 3-8% of the deionized water; in step ③, the amount of organic bismuth catalyst used is 0.1-0.2% of the total mass of silane; and in step ④, the amount of activated carbon used is 1-3% of the total mass of silane.

[0016] In one embodiment, the mass ratio of aluminum tripolyphosphate, nano-silica, and carboxylated multi-walled carbon nanotubes in the modified functional composite filler is (35-40):(25-30):(5-10), and the amount of fluorinated hyperbranched polyoxysilane is 10-15% of the total mass of the three fillers.

[0017] In a preferred embodiment, the preparation of the modified functional composite filler includes the following steps: Aluminum tripolyphosphate, nano-silica, and carboxylated multi-walled carbon nanotubes were dispersed in anhydrous ethanol. Fluorinated hyperbranched polyoxysilane was added, and the mixture was heated to 70-75℃ and stirred for 6-8 hours. After the reaction was completed, the solid and liquid were separated. The obtained solid was washed (specifically, washed 2-3 times with anhydrous ethanol) and dried (specifically, vacuum dried at 78-82℃ for 10-14 hours) to obtain the modified functional composite filler.

[0018] In a preferred embodiment, during the preparation of the modified functional composite filler, the amount of water-ethanol used when dispersing the filler is 3-6 times the total mass of the filler.

[0019] In one embodiment, the crosslinking agent in the auxiliary reinforcing agent is at least one of divinylbenzene (DVB), ethylene glycol dimethacrylate (EGDMA), and trimethylolpropane trimethacrylate (TMPTMA), preferably ethylene glycol dimethacrylate (EGDMA). The platinum-catalyzed hydrosilylation system comprises vinyl-terminated polydimethylsiloxane and a hydrosilylation curing agent containing a Si-H crosslinking agent and a platinum catalyst. The vinyl-terminated polydimethylsiloxane is either Sylgard 184 component A or Sylgard 186 component A, preferably Sylgard 184 component A. The hydrosilylation curing agent containing a Si-H crosslinking agent and a platinum catalyst is either Sylgard 184 component B or Sylgard 186 component B, preferably Sylgard 184 component B. The mass ratio of the vinyl-terminated polydimethylsiloxane to the hydrosilylation curing agent containing a Si-H crosslinking agent and a platinum catalyst is 10:1. The ring-opening metathesis polymerization catalyst is any one of Grubbs 2nd catalyst, Grubbs 1st catalyst, Hoveyda-Grubbs catalyst, and Schrock catalyst, with Grubbs 2nd catalyst being preferred. The chain extender containing dynamic disulfide bonds is any one of IPDI-disulfide prepolymer, 4,4'-diaminodiphenyl disulfide (ODD), 2-hydroxyethyl disulfide (HEDS), and diallyl disulfide (DADS), preferably IPDI-disulfide prepolymer, which is obtained by reacting isophorone diisocyanate with 2,2'-diaminodiphenyl disulfide, wherein the molar ratio of isophorone diisocyanate to 2,2'-diaminodiphenyl disulfide is 2:1; The lubricant is any one of dimethyl silicone oil, methylphenyl silicone oil, or modified silicone oil, with dimethyl silicone oil being preferred.

[0020] In a preferred embodiment, the preparation of the IPDI-disulfide prepolymer includes the following steps: Isophorone diisocyanate and ethyl acetate are added to a reactor and mixed thoroughly. The temperature is raised to 60-70°C, and then a catalyst (preferably an organic bismuth catalyst, such as DY-20 from Shanghai Deyin Chemical Co., Ltd. or Borchi® Kat 24 from Borchers) is added and mixed thoroughly. Then, an ethyl acetate solution of 2,2'-diaminodiphenyl disulfide is slowly added dropwise over a period of 1-1.5 hours. After the addition is complete, the reaction is maintained at this temperature for 3-4 hours to obtain the IPDI-disulfide prepolymer.

[0021] In a preferred embodiment, during the preparation of the IPDI-disulfide prepolymer, the amount of catalyst used is 0.1-0.3% of the total mass of isophorone diisocyanate and 2,2'-diaminodiphenyl disulfide, and the amount of ethyl acetate used is 1-2 times the total mass of isophorone diisocyanate and 2,2'-diaminodiphenyl disulfide.

[0022] In a preferred embodiment, the auxiliary reinforcing agent is prepared by a ring-opening metamerization and hydrosilylation reaction of a raw material comprising 25-30 parts by weight of norbornyl dodecafluoroheptyl ester (NDF), 20-25 parts by weight of trifluoroethyl methacrylate (TFEMA), 6-10 parts by weight of dinorbornyl ethylene glycol ester (NEG), 2-3 parts by weight of a crosslinking agent, 13.2-17.6 parts by weight of a platinum-catalyzed hydrosilylation system (e.g., 12-16 parts by weight of Sylgard 184 component A + 1.2-1.6 parts by weight of Sylgard 184 component B), 0.3-0.4 parts by weight of a ring-opening metamerization catalyst (e.g., Grubbs 2nd catalyst), 5-8 parts by weight of a chain extender containing dynamic disulfide bonds (e.g., IPDI-disulfide prepolymer), and 25-35 parts by weight of a lubricant (e.g., dimethyl silicone oil).

[0023] In a preferred embodiment, the preparation of the auxiliary reinforcing agent includes the following steps: Norbornene dodecafluoroheptyl ester (NDF), trifluoroethyl methacrylate (TFEMA), dinorbornene ethylene glycol ester (NEG), crosslinking agent, vinyl-terminated polydimethylsiloxane, and lubricant are dissolved in dichloromethane. Then, a chain extender containing dynamic disulfide bonds is added, and nitrogen gas is purged for oxygen removal for 10-20 minutes. Next, a ring-opening metathesis polymerization catalyst, a hydrosilylation curing agent containing Si-H crosslinking agent and platinum catalyst are added, and the reaction is carried out at room temperature for 10-14 hours. Finally, the mixture is cured at 55-65℃ for 1.5-2.5 hours to obtain the auxiliary reinforcing agent.

[0024] In a preferred embodiment, the mass ratio of dichloromethane to the total amount of reaction raw materials is (0.5-1.5):1.

[0025] A method for preparing an anti-icing coating suitable for wind turbine blades includes the following steps: a) Mix the fluorosilicone-acrylic hybrid resin, dispersant and part of the solvent evenly, then add the modified functional composite filler, polytetrafluoroethylene micro powder and auxiliary reinforcing agent, mix evenly, then add the leveling agent and the remaining solvent, mix evenly, grind, filter and discharge to obtain component A; b) Mix component A and component B in a specific ratio to obtain an anti-icing coating suitable for wind turbine blades.

[0026] Compared with the prior art, the present invention has the following significant advantages: The coating provided by this invention has excellent anti-icing function, weather resistance, corrosion resistance, and wear resistance. Its comprehensive performance is excellent and can well meet the application requirements of anti-icing coatings for wind turbine blades, thus having great industrial application value. Detailed Implementation

[0027] The technical solution of the present invention will be further described in detail and completely below with reference to the embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the manufacturer. Example 1

[0028] 1) Preparation of fluorosilicone-acrylic hybrid resin 1) Methyl methacrylate (MMA, 35.0g, Mitsubishi Chemical, Japan), isobornyl methacrylate (IBOMA, 12.0g, Mitsubishi Chemical, Japan), butyl acrylate (BA, 18.0g, Wanhua Chemical), tridecafluorooctyl methacrylate (PFOMA, 12.0g, Harbin Xuejia Fluorosilicon Chemical), vinyl-terminated fluorosilicone oil (Vi-PDMS-F, Mn≈3000, vinyl content 0.8mmol / g, 8.0g, Shandong Dayi Chemical), hydroxyethyl methacrylate (HEMA, 6.0g, Mitsubishi Chemical, Japan), and glycidyl methacrylate (GMA, 3.0g, Mitsubishi Chemical, Japan) were mixed evenly to obtain a monomer mixture (total 94.0g). Azobisisobutyronitrile (AIBN, 0.6 g, Shanghai Maclean Biochemical Technology) was dissolved in a mixed solvent of propylene glycol methyl ether acetate / butyl acetate (1:1, 25.0 g) and stirred until completely dissolved to obtain an initiator solution. 2) Add a propylene glycol methyl ether acetate / butyl acetate (1:1, 100.0g) mixed solvent to the reactor, heat to 80℃, purge with nitrogen three times to maintain nitrogen protection, and simultaneously add the monomer mixture (dropping time 2.5 hours) and 80% of the initiator solution (dropping time 3 hours). Maintain the reaction temperature at 80℃ during the dropping process. After the dropping is complete, keep the reaction at this temperature for 2.5 hours, then add the remaining 20% ​​of the initiator solution, continue to keep the temperature at this temperature for 1.5 hours, cool to below 60℃, filter and discharge to obtain a fluorosilicone-acrylic hybrid resin with a solid content of approximately 48%.

[0029] (ii) Preparation of fluorinated hyperbranched polyoxysilanes ① Add γ-glycidyl etheroxypropyltrimethoxysilane (KH-560, 47.2g, 0.2mol, Nanjing Nengde New Material Technology Co., Ltd.) and ethanol / ethyl acetate (volume ratio 1:2) mixed solvent (200mL) to a glass reactor, under nitrogen protection, and stir at 55℃ for 30 minutes; ② Add an aqueous solution of acetic acid with pH=4.5 (35g of deionized water and 1.5g of glacial acetic acid) dropwise over 1 hour, and then react at 72℃ for 3 hours after the addition is complete; ③ Slowly add perfluorodecyltrimethoxysilane (FDTS, 72.5g, 0.125mol, Harbin Xuejia Fluorosilicon Chemical), hexadecyltrimethoxysilane (HDTMS, 35.6g, 0.1mol, Qufu Chenguang Chemical) and triethoxysilylpropylphosphonic acid (14.5g, 0.05mol, Hubei Xinmingtai Chemical), stir for 15 minutes, add organobismuth catalyst (Borchi Kat 24, 0.2g, Borchers GmbH, Germany), and continue the reaction at 72℃ for 3 hours; ④ Cool to 55℃, add activated carbon (3g), stir for 30 minutes, filter, and distill the filtrate under reduced pressure (-0.095MPa, 90℃) to obtain a light yellow viscous liquid, which is fluorinated hyperbranched polyoxysilane (HBP-Si-F).

[0030] (III) Preparation of modified functional composite fillers Dry aluminum tripolyphosphate (ATP, 38.0 g, Wuhan Haishi Chemical Co., Ltd.), nano silica (28.0 g, Evonik Degussa), and carboxylated multi-walled carbon nanotubes (MWCNTs-COOH, 8.0 g, Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.) were dispersed in anhydrous ethanol (350 mL), ultrasonically dispersed for 30 minutes, stirred for 30 minutes, and then fluorinated hyperbranched polyoxysilane (HBP-Si-F, 11.1 g, 15% of the total filler mass) was added. The mixture was heated to 72 °C and stirred for 8 hours. After the reaction was completed, the mixture was centrifuged (6000 rpm, 15 minutes), washed three times with anhydrous ethanol, vacuum dried at 80 °C for 12 hours, and ground through a 200-mesh sieve to obtain the modified functional composite filler.

[0031] (iv) Preparation of auxiliary reinforcing agents 1) Preparation of IPDI-disulfide prepolymer: Isophorone diisocyanate (IPDI, 44.5 g, 0.2 mol, Wanhua Chemical) and ethyl acetate (80 g) were added to a reactor and mixed thoroughly. The mixture was heated to 65 °C, and an organic bismuth catalyst (DY-20, 0.1 g, Shanghai Deyin Chemical) was added. An ethyl acetate solution (80 g) of 2,2'-diaminodiphenyl disulfide (DTDA, 24.8 g, 0.1 mol, Shanghai Maclean Biochemical Technology) was slowly added dropwise over 1.5 hours. After the addition was complete, the mixture was kept at this temperature for 3.5 hours to obtain IPDI-disulfide prepolymer (solid content approximately 40%). 2) Preparation of auxiliary reinforcing agents: Norborneol-based dodecafluoroheptyl ester (NDF, 28.0 g, Harbin Xuejia Fluorosilicone Chemical), trifluoroethyl methacrylate (TFEMA, 22.0 g, Harbin Xuejia Fluorosilicone Chemical), dinorborneol-based ethylene glycol ester (NEG, 8.0 g, prepared according to the method in patent CN114656594B), ethylene glycol dimethacrylate (EGDMA, 2.5 g, Shanghai Maclean Biochemical Technology), Sylgard 184 component A (14.0 g, Dow Corning Incorporated), and dimethyl silicone oil (30.0 g, 50 mPa·s, Dow Corning) were dissolved in dichloromethane (100 g), stirred until dissolved, and IPDI-disulfide prepolymer (6.0 g on solids, actual feed 15.0 g) was added. Nitrogen gas was purged for 15 minutes to remove oxygen, and then Grubbs 2nd catalyst (0.35 g, Shanghai Maclean Biochemical Technology) and Sylgard 184 were added. Component B (1.4g, Dow Corning, USA) was reacted at room temperature for 12 hours, and then cured at 60°C for 2 hours to obtain the auxiliary reinforcing agent.

[0032] (v) Preparation of anti-icing coatings suitable for wind turbine blades a) Add 30.0 parts by weight of fluorosilicone-acrylic hybrid resin, 1.0 part by weight of dispersant BYK-163 (BYK Chemicals, Germany), and 15.0 parts by weight of propylene glycol methyl ether acetate / butyl acetate (1:1) mixed solvent to a dispersion tank and stir at 500 rpm for 15 minutes. Slowly add 40.0 parts by weight of modified functional composite filler, 5.0 parts by weight of polytetrafluoroethylene micro powder (average particle size 3-5 μm, Shanghai Sanaifu), and auxiliary reinforcing agent (10.0 parts by weight). Stir at 900 rpm for 45 minutes. Add 0.5 parts by weight of leveling agent BYK-333 (BYK Chemicals, Germany) and the remaining mixed solvent (15.0 parts by weight), and continue stirring for 15 minutes. Grind the mixture in a sand mill until the fineness is ≤30 μm, filter, and obtain component A. b) Mix component A and component B (elastic polyurethane curing agent, HDI trimer, Wanhua Chemical) at a mass ratio of 8:1 to obtain an anti-icing coating (component A and component B are stored separately in daily life. When needed, mix component A and component B evenly on site before use). Example 2

[0033] The difference between this embodiment and Example 1 is that the content of each component in the anti-icing coating formulation is different. The specific formulation is as follows: 25.0 parts by weight of fluorosilicone-acrylic hybrid resin, 45.0 parts by weight of modified functional composite filler, 4.0 parts by weight of polytetrafluoroethylene micro powder, 8.0 parts by weight of auxiliary reinforcing agent, 0.8 parts by weight of BYK-163 dispersant, 0.4 parts by weight of BYK-333 leveling agent, and 25.0 parts by weight of propylene glycol methyl ether acetate / butyl acetate (1:1) mixed solvent. The mass ratio of component A to component B is 7:1, and the rest is the same as in Example 1. Example 3

[0034] The difference between this embodiment and Example 1 is that the content of each component in the anti-icing coating formulation is different. The specific formulation is as follows: 35.0 parts by weight of fluorosilicone-acrylic hybrid resin, 35.0 parts by weight of modified functional composite filler, 6.0 parts by weight of polytetrafluoroethylene micro powder, 12.0 parts by weight of auxiliary reinforcing agent, 1.2 parts by weight of BYK-163 dispersant, 0.6 parts by weight of BYK-333 leveling agent, and 35.0 parts by weight of propylene glycol methyl ether acetate / butyl acetate (1:1) mixed solvent. The mass ratio of component A to component B is 9:1, and the rest is the same as in Example 1.

[0035] Comparative Example 1 The difference between this comparative example and Example 1 is as follows: In the anti-icing coating, commercially available fluorosilicone resin (Daikin Fluorochemicals, GK-570) is used to replace the fluorosilicone-acrylic hybrid resin in Example 1, and a composite filler of unmodified aluminum tripolyphosphate, nano-silica and carboxylated multi-walled carbon nanotubes is used to replace the modified functional composite filler in Example 1. The rest is the same as in Example 1.

[0036] Comparative Example 2 The difference between this comparative example and Example 1 is as follows: The anti-icing coating does not contain any auxiliary reinforcing agents; otherwise, it is the same as in Example 1.

[0037] Comparative Example 3 The difference between this comparative example and Example 1 is as follows: The anti-icing coating does not contain polytetrafluoroethylene powder, and the modified functional composite filler does not contain aluminum tripolyphosphate; otherwise, it is the same as in Example 1.

[0038] Comparative Example 4 The difference between this comparative example and Example 1 is as follows: In the anti-icing coating, a composite filler obtained by modifying aluminum tripolyphosphate, nano-silica, and carboxylated multi-walled carbon nanotubes with the traditional small molecule silane coupling agent γ-glycidoxypropyltrimethoxysilane (KH-560) is used instead of the modified functional composite filler obtained by modifying with fluorinated hyperbranched polyoxysilane in Example 1. The rest is the same as in Example 1.

[0039] Performance testing: The anti-icing coatings prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests according to relevant standards, specifically as follows: Water contact angle test: According to GB / T 30447-2013 standard, a contact angle measuring instrument was used, with 5μL of deionized water as the test liquid, and the measurements were taken at 5 different positions on the sample surface, and the average value was taken. Freezing delay time test: Place the sample on a -15℃ low temperature test bench and pre-cool it until the temperature is stable. Drop 10μL of deionized water onto the sample surface and record the time from when the water droplet contacts the surface to when it is completely frozen. Test each sample 5 times and take the average value. Ice adhesion strength test: Referring to HG / T 5367.5-2022 standard, a cylindrical mold with an inner diameter of 20mm and a height of 10mm is placed on the coating surface, deionized water is injected, and the mold is frozen at -20℃ for 24 hours. The maximum force required for the ice to detach from the coating is measured using a tensile testing machine at a tensile speed of 10mm / min. The ice adhesion strength is calculated. Each sample is tested 5 times, and the average value is taken. Adhesion test: In accordance with GB / T 5210-2006 standard, the adhesion between the coating and the substrate is tested by the pull-off method. Using an adhesive strength tester, the test column is bonded to the coating and then stretched vertically until the coating peels off. The maximum tensile force value is recorded. Abrasion resistance test: According to GB / T 1768-2006 standard, the Taber abrasion tester was used with CS-10 grinding wheel, load 1kg, speed 60r / min, test 1000 revolutions, weigh the mass difference of the sample before and after the test, and calculate the wear amount; Salt spray corrosion resistance test: According to GB / T 1771-2007 standard, the sample is placed in a salt spray test chamber, the spray medium is 5% NaCl solution, the test temperature is 35±2℃, and the spray is continuous for 1500 hours. Observe whether the coating surface shows blistering, rust, peeling and other phenomena. UV aging resistance test: In accordance with GB / T 1865-2009 standard, the QUV UV aging test machine was used, with UVA-340 lamp tube, irradiance of 0.83W / m², and cyclic conditions: 4 hours of light exposure at 60℃, 4 hours of condensation at 50℃, and a total test time of 2000 hours. The water contact angle of the coating was measured before and after the test, and the contact angle retention rate was calculated. The test results are shown in Table 1.

[0040] Table 1 Performance test data of the coatings prepared in Examples 1-3 and Comparative Examples 1-4

[0041] As shown in Table 1, the coatings prepared in Examples 1-3 exhibit the following characteristics: water contact angles of 154.8-157.5°, all reaching superhydrophobic levels (>150°); freezing delay time of 652-710 seconds (-15℃); and ice adhesion strength of 30.5-35.2 kPa, indicating excellent anti-icing properties. Adhesion of 10.5-11.8 MPa indicates strong bonding between the coating and the substrate. Abrasion resistance of 35-42 mg / 1000 r indicates excellent abrasion resistance. No blistering or peeling after 1500 hours of salt spray testing indicates excellent corrosion resistance. After 2000 hours of UV aging, the contact angle retention rate reaches 83-88%, indicating good weather resistance. Overall, the coatings demonstrate excellent performance and can meet the requirements for anti-icing coatings for wind turbine blades. Furthermore, as can be seen from the table, the overall performance of the coatings prepared in Examples 1-3 is significantly better than that of the coatings prepared in Comparative Examples 1-4. This may be because: 1) Compared with Comparative Example 1: Comparative Example 1 uses a composite filler made by simply physically mixing commercially available fluorosilicone resin with unmodified aluminum tripolyphosphate, nano-silica, and carboxylated multi-walled carbon nanotubes. Specifically: the commercially available fluorosilicone resin lacks functional groups in the acrylic acid segments, resulting in deficiencies in its mechanical properties and anchoring properties with the filler; the unmodified filler, due to its high surface energy and large polarity difference, severely aggregates in the resin matrix, failing to form an effective micro / nano rough structure, leading to insufficient hydrophobicity and high ice adhesion strength; furthermore, the unmodified aluminum tripolyphosphate is unevenly dispersed in the resin matrix and has weak interfacial bonding with the resin, failing to fully exert its active anti-corrosion function; the unmodified aluminum tripolyphosphate severely aggregates in the resin matrix, failing to form an effective three-dimensional photothermal conductive network, resulting in low photothermal conversion efficiency and high ice adhesion strength. The embodiment uses a fluorosilicone-acrylic hybrid resin, which connects the fluorinated segments and acrylic segments with chemical bonds through free radical copolymerization. At the same time, isobornyl methacrylate (IBOMA, providing rigidity and weather resistance), hydroxyethyl methacrylate (HEMA, providing hydroxyl crosslinking sites), and glycidyl methacrylate (GMA, providing epoxy anchoring sites) are introduced to achieve molecular-level synergy of low surface energy, mechanical properties, crosslinking reactivity, and filler anchoring. Meanwhile, fluorinated hyperbranched polyoxysilane is used to jointly modify the three fillers. The hyperbranched macromolecules form a three-dimensional network coating layer on the filler surface. Through multi-site covalent bond anchoring, on the one hand, the hydrophilic silica and aluminum tripolyphosphate surfaces are transformed into hydrophobic surfaces. On the other hand, the carboxylated multi-walled carbon nanotubes are effectively separated through the steric hindrance effect, realizing the nanoscale uniform dispersion of the three fillers and forming a stable micro-nano rough structure and superhydrophobic state. 2) Compared with Comparative Example 2: Comparative Example 2 does not contain auxiliary reinforcing agents, while the fluorinated norbornene monomers (NDF, TFEMA) and PDMS segments in the auxiliary reinforcing agents have low surface energy characteristics, which can synergistically improve the hydrophobic properties of the coating; dimethyl silicone oil can form a lubricating layer on the coating surface, reducing the adhesion strength of ice; the flexible network and dynamic disulfide bonds of PDMS can effectively dissipate frictional energy and improve wear resistance; the fluorinated segments have good UV resistance and can delay coating aging; therefore, after Comparative Example 2 lacks auxiliary reinforcing agents, the initial hydrophobic properties, anti-icing properties, mechanical properties and weather resistance of the coating all decrease. 3) Compared with Comparative Example 3: Comparative Example 3 did not add polytetrafluoroethylene (PTFE) micropowder, and the modified functional composite filler did not add aluminum tripolyphosphate. The absence of PTFE micropowder resulted in an incomplete micro-nano rough structure of the coating, which could not form a stable superhydrophobic state, leading to a decrease in water contact angle and an increase in ice adhesion strength. In addition, PTFE micropowder has self-lubricating properties, and its absence resulted in the loss of the coating's self-lubricating properties, which in turn led to a decrease in wear resistance. The absence of aluminum tripolyphosphate caused the coating to lose its active chemical passivation and corrosion protection capabilities, and the physical barrier of the resin alone could not effectively resist salt spray corrosion. Furthermore, the absence of aluminum tripolyphosphate resulted in an incomplete composite network of aluminum tripolyphosphate, silica, and carboxylated multi-walled carbon nanotubes, which affected the overall mechanical properties of the coating. 4) Compared with Comparative Example 4: Comparative Example 4 used the traditional small molecule silane coupling agent KH-560 to replace the fluorinated hyperbranched polyoxysilane of the example to modify the filler. The small molecule coupling agent can only form a monomolecular interface layer and cannot effectively buffer stress, resulting in insufficient bonding strength between the filler and the resin interface. KH-560 does not contain perfluorinated segments, so it cannot impart ultra-low surface energy characteristics to the filler, resulting in reduced hydrophobicity. KH-560 does not contain phosphonic acid groups, resulting in reduced anti-corrosion function. The small molecule coupling agent has limited dispersion effect on the filler, resulting in an incomplete three-dimensional photothermal network, which in turn leads to higher ice adhesion strength. The fluorinated hyperbranched polyoxysilane used in the embodiments has a three-dimensional network topology, which can form a multi-site covalent anchoring and steric hindrance layer on the filler surface. At the same time, the introduction of perfluorinated segments (ultra-low surface energy), phosphonic acid groups (auxiliary corrosion protection) and long-chain alkyl groups (compatible with resin) can realize the all-round functional modification of the filler, thereby significantly improving the performance of the coating in all aspects. In summary, in the embodiments of the present invention, the fluorosilicone-acrylic hybrid resin, the fluorinated hyperbranched polyoxysilane modified composite filler, the auxiliary reinforcing agent, and other components have a good synergistic effect, which makes the coating in the embodiments superior to the comparative example in all aspects, with excellent comprehensive performance, and can well meet the application requirements of anti-icing coating for wind turbine blades.

[0042] Finally, it should be noted that the above are only some preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention shall fall within the scope of protection of the present invention.

Claims

1. An anti-icing coating suitable for wind turbine blades, characterized in that, The product comprises component A and component B, wherein the mass ratio of component A to component B is (6-10):1; component A is prepared from the following raw materials in parts by mass: Fluorosilicone-acrylic hybrid resin: 25-35 parts by weight; Modified functional composite filler: 35-45 parts by weight; Polytetrafluoroethylene micro powder: 3-6 parts by weight; Auxiliary reinforcing agent: 5-12 parts by weight; Dispersant: 0.5-1.5 parts by weight; Leveling agent: 0.2-0.8 parts by weight; Solvent: 20-40 parts by weight; Component B is an elastic polyurethane curing agent; The fluorosilicone-acrylic hybrid resin is obtained by free radical copolymerization of a monomer composition comprising methyl methacrylate, isobornyl methacrylate, butyl acrylate, tridecafluorooctyl methacrylate, vinyl-terminated fluorosilicone oil, hydroxyethyl methacrylate and glycidyl methacrylate. The modified functional composite filler is obtained by modifying aluminum tripolyphosphate, nano-silica, and carboxylated multi-walled carbon nanotubes with fluorinated hyperbranched polyoxysilane; the fluorinated hyperbranched polyoxysilane is obtained by the hydrolysis and condensation reaction of γ-glycidoxypropyltrimethoxysilane, perfluorodecyltrimethoxysilane, hexadecyltrimethoxysilane, and triethoxysilylpropylphosphonic acid. The auxiliary reinforcing agent is prepared by a combination of ring-opening metamerization and hydrosilylation reaction of raw materials comprising norbornene dodecafluoroheptyl ester, trifluoroethyl methacrylate, dinorbornene ethylene glycol ester, crosslinking agent, platinum-catalyzed hydrosilylation system, ring-opening metamerization catalyst, chain extender containing dynamic disulfide bonds, and lubricant.

2. The anti-icing coating for wind turbine blades according to claim 1, characterized in that, The monomer ratio in the fluorosilicone-acrylic hybrid resin is as follows: methyl methacrylate 30-40 parts by weight, isobornyl methacrylate 10-15 parts by weight, butyl acrylate 15-20 parts by weight, tridecafluorooctyl methacrylate 10-15 parts by weight, vinyl-terminated fluorosilicone oil 5-10 parts by weight, hydroxyethyl methacrylate 5-8 parts by weight, and glycidyl methacrylate 2-5 parts by weight.

3. The anti-icing coating for wind turbine blades according to claim 2, characterized in that, The preparation of the fluorinated hyperbranched polyoxysilane includes the following steps: ① Add γ-glycidyl etheroxypropyltrimethoxysilane and solvent to the reaction vessel, under nitrogen protection, and stir at 50-60℃ for 20-40 minutes; ② Add an aqueous solution of acetic acid with a pH of 4-5 dropwise over a period of 0.5-1.5 hours. After the addition is complete, allow the mixture to react at 70-75°C for 2.5-3.5 hours. ③ Slowly add perfluorodecyltrimethoxysilane, hexadecyltrimethoxysilane and triethoxysilylpropylphosphonic acid, stir for 10-20 minutes, then add the organic bismuth catalyst, and continue the reaction at 70-75℃ for 2.5-3.5 hours; ④ Cool to 50-60℃, add activated carbon, stir for 20-40 minutes, filter, and distill the filtrate under reduced pressure to obtain fluorinated hyperbranched polyoxysilane.

4. The anti-icing coating for wind turbine blades according to claim 1, characterized in that, In the fluorinated hyperbranched polyoxysilane, the molar ratio of γ-glycidoxypropyltrimethoxysilane: perfluorodecyltrimethoxysilane: hexadecyltrimethoxysilane: triethoxysilylpropylphosphonic acid is (3.0-5.0): (2.0-3.0): (1.5-2.5): (0.5-1.5).

5. The anti-icing coating for wind turbine blades according to claim 4, characterized in that, The preparation of the fluorinated hyperbranched polyoxysilane includes the following steps: ① Add γ-glycidyl etheroxypropyltrimethoxysilane and solvent to the reaction vessel, under nitrogen protection, and stir at 50-60℃ for 20-40 minutes; ② Add an aqueous solution of acetic acid with a pH of 4-5 dropwise over a period of 0.5-1.5 hours. After the addition is complete, allow the mixture to react at 70-75°C for 2.5-3.5 hours. ③ Slowly add perfluorodecyltrimethoxysilane, hexadecyltrimethoxysilane and triethoxysilylpropylphosphonic acid, stir for 10-20 minutes, then add the organic bismuth catalyst, and continue the reaction at 70-75℃ for 2.5-3.5 hours; ④ Cool to 50-60℃, add activated carbon, stir for 20-40 minutes, filter, and distill the filtrate under reduced pressure to obtain fluorinated hyperbranched polyoxysilane.

6. The anti-icing coating for wind turbine blades according to claim 1, characterized in that, In the modified functional composite filler, the mass ratio of aluminum tripolyphosphate, nano silica and carboxylated multi-walled carbon nanotubes is (35-40):(25-30):(5-10), and the amount of fluorinated hyperbranched polyoxysilane is 10-15% of the total mass of the three fillers.

7. The anti-icing coating for wind turbine blades according to claim 6, characterized in that, The preparation of the modified functional composite filler includes the following steps: Aluminum tripolyphosphate, nano-silica, and carboxylated multi-walled carbon nanotubes were dispersed in anhydrous ethanol, and fluorinated hyperbranched polyoxysilane was added. The mixture was heated to 70-75℃ and stirred for 6-8 hours. After the reaction was completed, the solid and liquid were separated, and the resulting solid was washed and dried to obtain the modified functional composite filler.

8. The anti-icing coating for wind turbine blades according to claim 1, characterized in that: In the auxiliary reinforcing agent, the crosslinking agent is at least one of divinylbenzene, ethylene glycol dimethacrylate, and trimethylolpropane trimethacrylate; The platinum-catalyzed hydrosilylation system includes vinyl-terminated polydimethylsiloxane and a hydrosilylation curing agent containing a Si-H crosslinking agent and a platinum catalyst, wherein the vinyl-terminated polydimethylsiloxane is either Sylgard 184 component A or Sylgard 186 component A, and the hydrosilylation curing agent containing a Si-H crosslinking agent and a platinum catalyst is either Sylgard 184 component B or Sylgard 186 component B; The ring-opening metathesis polymerization catalyst is any one of Grubbs 2nd catalyst, Grubbs 1st catalyst, Hoveyda-Grubbs catalyst, and Schrock catalyst; The chain extender containing dynamic disulfide bonds is any one of IPDI-disulfide prepolymer, 4,4'-diaminodiphenyl disulfide, 2-hydroxyethyl disulfide, and diallyl disulfide. The IPDI-disulfide prepolymer is obtained by reacting isophorone diisocyanate with 2,2'-diaminodiphenyl disulfide. The lubricant is any one of dimethyl silicone oil, methylphenyl silicone oil, or modified silicone oil.

9. The anti-icing coating for wind turbine blades according to claim 8, characterized in that: The preparation of the auxiliary reinforcing agent includes the following steps: Norbornene dodecafluoroheptyl ester, trifluoroethyl methacrylate, dinorbornene ethylene glycol ester, crosslinking agent, vinyl-terminated polydimethylsiloxane, and lubricant are dissolved in dichloromethane. Then, a chain extender containing dynamic disulfide bonds is added, and nitrogen is purged for oxygen removal for 10-20 minutes. Next, a ring-opening metathesis polymerization catalyst, a hydrosilylation curing agent containing Si-H crosslinking agent and platinum catalyst are added. The reaction is carried out at room temperature for 10-14 hours, and then cured at 55-65℃ for 1.5-2.5 hours to obtain the auxiliary reinforcing agent.

10. A method for preparing the anti-icing coating for wind turbine blades according to claim 1, characterized in that, Includes the following steps: a) Mix the fluorosilicone-acrylic hybrid resin, dispersant and part of the solvent evenly, then add the modified functional composite filler, polytetrafluoroethylene micro powder and auxiliary reinforcing agent, mix evenly, then add the leveling agent and the remaining solvent, mix evenly, grind, filter and discharge to obtain component A; b) Mix component A and component B in a specific ratio to obtain an anti-icing coating suitable for wind turbine blades.

Citation Information

Patent Citations

  • Negative plate grid and preparation method thereof

    CN120033214A

  • Acrylic acid modified polysiloxane super-hydrophobic anti-icing and active deicing coating and preparation method thereof

    CN120536042A